2015
DOI: 10.1016/j.pharep.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the route of administration of gold nanoparticles on their tissue distribution and basic biochemical parameters: In vivo studies

Abstract: Accumulation of those nanoparticles effect in increases of FRAP and glucose level up to 27% and 73%, respectively. This in turn suggests that iv administration of AuNPs may effect in serious medical complications. On the other site, the accumulation in the liver of about 50% of introduced particles to the rats body is promising for phototherapy and it opens "door" for drug transport to this organ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 26 publications
3
42
0
Order By: Relevance
“…29,35 To examine the biocompatibility of PGNPs and SGNPs, their influence on blood biochemistry and liver and kidney function was studied in albino rabbits. All rabbits survived during the 3-day study period, and no change was observed in normal behavior, food intake, and Direct cT scan image of (A) PgNPs and (B) sgNPs shows that porous shape has a better density value and thus better contrast display.…”
Section: Results and Discussion Shape And Surface Morphology Of Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,35 To examine the biocompatibility of PGNPs and SGNPs, their influence on blood biochemistry and liver and kidney function was studied in albino rabbits. All rabbits survived during the 3-day study period, and no change was observed in normal behavior, food intake, and Direct cT scan image of (A) PgNPs and (B) sgNPs shows that porous shape has a better density value and thus better contrast display.…”
Section: Results and Discussion Shape And Surface Morphology Of Npsmentioning
confidence: 99%
“…AST and ALP are studies. 29,35 However, this effect seems to be reversible as both the kidneys and liver revert to their normal function after clearance of nanoparticles ( Figure 6). Lack of toxicity has been broadly documented for negatively charged GNPs (probably due to their bare surface) in the size range reported in this paper and at a dose of 1 mg/kg.…”
Section: Results and Discussion Shape And Surface Morphology Of Npsmentioning
confidence: 99%
“…[6] Indeed, some AuNPs formulations have already been proposed as novel tools for in vitro and in vivo molecular imaging and drug delivery. [7] AuNPs have, for example, attracted interest as carriers to enhance the oral absorption of drugs and vaccines that are either poorly absorbed or are susceptible to gastrointestinal degradation. [8] However, to our knowledge, only AuNPs used for local heat generation in the plasmonic photothermal therapy of atherosclerosis and cancer have, to date, reached clinical stage (ClinicalTrials.gov Identifiers NCT01270139, NCT01679470, NCT00848042, NCT00436410).…”
Section: Introductionmentioning
confidence: 99%
“…During radiation, when cancerous cells are exposed to photons, a certain phenomenon, called photoelectric effect, occurs which absorbs a significant amount of the colliding radiation [187].…”
Section: Brain Targetsmentioning
confidence: 99%